INTERNAL AUDIT WORK UNIT STRATEGY IN SUPERVISING SHARIA COMPLIANCE IN SHARIA BANKING - Prihardini, Firna Maristha; Andriani, Sri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to identify the strategy of the internal audit function carried out by Satuan Kerja Audit Internal (SKAI) in implementing sharia compliance supervision at Bank X. Qualitative research with a case study approach was used in this research to reach the research objective. Furthermore, research data was collected using semi-structured interviews and documentation technique. The research results found that the Satuan Kerja Audit Internal (SKAI) and the Sharia Supervisory Board (SSB) carried out sharia combined assurance as a strategy in monitoring sharia compliance. The limited competence of SKAI internal auditors is overcome by the sharia competence of SSB. This research encourages internal auditors to continue developing their competencies in accordance with the scope of their internal audit activities. This research also encourages regulators to facilitate internal auditors with sharia competency certification to support their position and role on sharia compliance supervision in sharia banking